AB0863 High Frequency of Caps and Traps in Russian Patients with Systemic Juvenile Idiopathic Arthritis. (15th July 2016) - Alexeeva, E.; Savostyanov, K.; Sleptsova, T.; Pushkov, A.; Bzarova, T.; Valieva, S.; Denisova, R.; Isayeva, K.; Chistyakova, E.; Lomakina, O.; Soloshenko, M.; Kaschenko, E.
Abstract : Background: The main clinical manifestations of monogenic autoinflammatory syndromes and polygenic Systemic juvenile idiopathic arthritis (sJIA) are similar and presented with fever, migratory erythematous rash, arthritis/arthralgia and eye manifestations. The right diagnosis is reached using gene analysis and prognosis depends on correct personified therapy. Objectives: To evaluate frequency of CAPS and TRAPS in Russian systemic JIA pts. Methods: 170 pts (61 boys, 109 girls) at the age from 1 to 17y. (6.9 (3.9;9.4) followed with a diagnosis of sJIA were selected according to the clinical manifestations, with subsequent obligatory genetic counseling in the Department of Rheumatology of the Scientific Center for Children's Health. The median age of disease onset was 2.9 (1.2;6.0)y., disease duration – 4.0 (2.6;5.4)y. The commonest features were fever (100%), arthritis/arthragia (100%), rash (163 pts/96%), hepato- and splenomegaly (160/94%), lymphadenopathy (136/80%), headache (88/52%), abdominal pain (98/58%) and eye manifestations (42/25%). Patients' DNA was sequenced in all coding exons and intronic flanks of the TNFRSF1A and NLRP3 genes. Results: In 18/130 (10.6%) pts genetic autoinflammatory syndrome was established. In 12 pts we found mutations in TNFRSF1A: In 9/12 pts - the most frequent mutations c.362G>A (p.R92Q) located in exon 4 and associated with the mild progression of TRAPS. One pt revealed a TNFRSF1A mutation c.374G>A (C96Y). Two pts identified mutations which were not previously described in the databases. They had TNFRSF1A deletion c.337_339del (p.Glu113del) and frameshift mutation c.792delT (p.Lys265Serfs*87) located in exons 04 and 09 of TNFRSF1A gene, respectively. The median age of disease onset was 5.3 y. Pts had a median 85 symptomatic days per year, attacks were recurrent in 78%. A family history was present in 3 pts: 2 girls with R92Q and one – with C96Y mutation. Four pts identified mutations in NLRP3 gene. One pt had mutation c.598G>A (p.Val200Met). Three pts had mutations which were not previously described in the databases. One pt had a mutation c.796C>T (p.Leu266Phe) in exon 04 of NLRP3 gene. Two other pts had mutations c.2861C>T and c.2173C>A, respectively. Pts with c.2173C>A and c.796C>T mutations have CINCA/NOMID phenotype and dramatic effect of canacinumab. 2 pts presented changes in both genes. They had R92Q mutation in TNFRSF1A and polymorphism Q705K in NLRP3 gene. In 15 (7.6%) pts we identified NLRP3 gene polymorphism Q705K associated with elevated levels of IL1. Conclusions: Our results suggests for a relatively frequent incidence of CAPS and TRAPS in Russian systemic JIA pts. The number of genetically confirmed pts with periodic fever syndromes in Russia is very low. It is important to establish a network for genetic testing of periodic fever syndromes. Disclosure of Interest: E. Alexeeva Grant/research support from: Roche, Novartis, UCB, K. Savostyanov Grant/research support from: Novartis, T. Sleptsova Grant/research support from: Novartis, UCB, A. Pushkov Grant/research support from: Novartis, T. Bzarova Grant/research support from: Pfizer, S. Valieva Grant/research support from: Roche, R. Denisova Grant/research support from: Roche, Novartis, Pfizer, UCB, K. Isayeva Grant/research support from: Roche, Novartis, E. Chistyakova: None declared, O. Lomakina: None declared, M. Soloshenko: None declared, E. Kaschenko: None declared